Pengaruh Net Profit Margin, Debt Equity Ratio dan Current Ratio Terhadap Harga Saham Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2023 - Yohanes Calvin; Nurhadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study is based on the large public attention to investment, especially to investment instruments such as stocks. In addition, the trend of a healthy lifestyle that is currently popular and the health transformation carried out by the government make the shares of health sector companies interesting to pay attention to. This study was aims to analyze and determine the effect of Net Profit Margin (NPM), Debt to Equity Ratio (DER) and Current Ratio (CR) simultaneously or partially on stock prices. The research method used in this study is a quantitative research method. The population used in this study were companies in the health sector listed on the Indonesia Stock Exchange in 2020-2023. There are 33 companies in the health sector listed on the Indonesia Stock Exchange. The sampling technique in this study used a purposive sampling technique with the number of selected company samples being 11 companies. The data used in this study are secondary data from financial data on the Indonesia Stock Exchange contained in the company's annual report. The variables tested in this study are Net Profit Margin (NPM), Debt to Equity Ratio (DER), Current Ratio (CR) and stock price. The data collection technique used in this study uses documentation techniques from the company's annual financial report. The data analysis technique used in this study is multiple linear regression.The results of this study show that Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Curretn Ratio (CR) Simultaneously have a significant effect on stock prices. Partially, Net Profit margin (NPM) and Debt to Equity Ratio (DER) partially does not have a significant effect on stock prices. Meanwhile, Current Ratio (CR) partially have a significant effect on stock prices.